Police Strategy to Tackle the Crime of Online Fraud: Strategi Kepolisian Menanggulangi Tindak Pidana Penipuan Online - Pratesta, Oxy Yudha; Pinem, Serimin; Zulyadi, Rizkan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Social media fraud is increasingly prevalent in the digital era, causing public concern and economic losses. Specific Background: Serdang Bedagai Regency in Indonesia is particularly vulnerable due to various local contributing factors. Knowledge Gap: In-depth studies analyzing the causes, criminal modus operandi, and local law enforcement responses to social media fraud from a criminological perspective remain limited. Aims: This study aims to examine the factors contributing to social media fraud in Serdang Bedagai, identify the perpetrators' methods, and evaluate the countermeasures taken by the Serdang Bedagai Police Resort. Results: The findings reveal that fraud is driven by economic hardship, a consumerist culture, limited digital literacy, a lack of public caution, and weak governmental oversight. The common fraud schemes include fake online loans, deceptive e-commerce transactions, and fictitious prize giveaways. The local police implement both penal approaches (criminal law enforcement) and non-penal strategies (preventive, cooperative, and educational efforts) to address the issue. Novelty: This study uniquely integrates a criminological framework with a normative juridical method, offering a localized analysis of digital fraud and its law enforcement responses. Implications: The results inform the development of community-based cybersecurity policies and enhance the effectiveness of digital crime prevention and prosecution in vulnerable regions. Highlights: Highlights localized factors influencing digital fraud in Serdang Bedagai. Identifies specific criminal schemes and police countermeasures. Offers a criminological and juridical perspective for policy formulation. Keywords: Social Media Fraud, Criminology, Law Enforcement, Digital Literacy, Cybercrime Prevention